EFEKTIFITAS E-LEARNING BERBASIS WEB SEBAGAI PENDUKUNG IN HOUSE TRAINING DALAM MENINGKATKAN KOMPETENSI PERAWAT DI RUMAH SAKIT MUHAMMADIYAH LAMONGAN - Suratmi Suratmi; Suwardi Suwardi (UNUSA Press, 2017)
Three domains nurse competention have been identified as cognitif, affective and psichomotor. One of the methods for improving nurse competention in hospital is by using inhouse training conventional or distance learning (e-learning) methods. The aim of this study were to determine the efficacy of nurse e-learning based on web for supporting inhouse training to improve competention of nurse Muhammadiyah Lamongan Hospital. This pre-experimental study using one group preposttest design and sampling methods using proportionate stratified random sampling. 31 responden were selected as on experiment. Duration of intervention is 1 week. The data were take by application based on web. This study showed improvement efficacy of nurse e-learning based on web for supporting inhouse training to improve competention of nurse in Muhammadiyah Lamongan Hospital. Level of significance (p)=0,00<α(0.05). Efficacy level at moderate-high, index gain value 0,6. Due to the result of this study, e-learning based on web can be used for supporting inhouse training, to improve competention of nurse in Muhammadiyah Lamongan Hospital.